The Arabidopsis 2′-O-Ribose-Methylation and Pseudouridylation Landscape of rRNA in Comparison to Human and Yeast - Streit, Deniz; Schleiff, Enrico (Frontiers in Plant Science, 2021)
Eukaryotic ribosome assembly starts in the nucleolus, where the ribosomal DNA (rDNA) is transcribed into the 35S pre-ribosomal RNA (pre-rRNA). More than two-hundred ribosomal biogenesis factors (RBFs) and more than two-hundred small nucleolar RNAs (snoRNA) catalyze the processing, folding and modification of the rRNA in Arabidopsis thaliana. The initial pre-ribosomal 90S complex is formed already during transcription by association of ribosomal proteins (RPs) and ribosome biogenesis factors (RBFs). In addition, small nucleolar ribonucleoprotein particles (snoRNPs) composed of snoRNAs and RBFs catalyze the two major rRNA modification types, 2´-O-ribose-methylation and pseudouridylation. Besides these two modifications, rRNAs can also undergo base methylations and acetylation. However, the latter two modifications have yet not yet been systematically explored in plants. The snoRNAs of these snoRNPs serve as targeting factors to direct modifications to specific rRNA regions by antisense elements. Today, hundreds of different sites of modifications in the rRNA are have been described for eukaryotic ribosomes in general. While our understanding of the general process of ribosome biogenesis is quitehas advanced rapidly, the diversities appearing during plant ribosome biogenesis is beginning tojust emerge. Today, more than two-hundred RBFs were identified by bioinformatics or biochemical approaches, including several plant specific factors. Similarly, more than two hundred snoRNA were predicted based on RNA sequencing experiments. Here, we discuss the predicted and verified rRNA modification sites and the corresponding identified snoRNAs on the example of the model plant Arabidopsis thaliana. Our summary uncovers the plant modification sites in comparison to the human and yeast modification sites.